THE DIFFICULTIES ENCOUNTERED BY THE SECOND GRADE STUDENTS OF SMA YPTB KETONG IN READING COMPREHENSION - Sudarto, Sudarto; Nadrun, Nadrun; Naniwarsih, Andi (Universitas Muhammadiyah Palu, 2020)
The objective of this research was to find out the difficulties in reading comprehension encountered by the second grade students of SMA YPTB Ketong. The researcher used descriptive method. The subject of this research was 24 students of the second grade of SMA YPTB Ketong. The data was collected by interviewing the students and the English teachers. The result of this research shows some findings. The result of questionnaire shows that 71% students who agree that they do not give more attention in reading text and 71% students who agree that they do not master grammar when reading a text as a higher percentage. Furthermore, the result of interview from the teachers shows that in the teaching process they do not know the name of the method, explain more and more because students get confused in understanding and translating the words in reading text. The student have insufficient vocabulary so that they find it difficult to understand reading comprehension, difficult in getting message from the reading text, to understand the teacher’s explanation and words in English that have more than one meaning.Keywords: Difficulties, Reading, and Comprehension.